2006
DOI: 10.1194/jlr.m600284-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic effects of P. aeruginosa involve inhibition of surfactant phosphatidylcholine synthesis

Abstract: Pseudomonas aeruginosa causes sepsis-induced acute lung injury, a disorder associated with deficiency of surfactant phosphatidylcholine (PtdCho). P. aeruginosa (PA103) utilizes a type III secretion system (TTSS) to induce programmed cell death. Herein, we observed that PA103 reduced alveolar PtdCho levels, resulting in impaired lung biophysical activity, an effect partly attributed to caspase-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Cleavage at this site in response to farnesol-induced apoptosis in CHO cells excluded CCTa from the nucleus but did not affect in vitro activity [185,218]. In contrast, caspase cleavage of CCTa in P. aeruginosa-infected murine lung epithelial cells was linked to decreased PC synthesis and apoptosis [219]. A more extensive analysis of inhibition of the CDP-choline pathway in apoptotic cells revealed that caspase 3 cleavage of CCTa is not required for inhibition of PC synthesis [218].…”
Section: Ccta Translocation Between Nuclear and Cytoplasmic Compartmentsmentioning
confidence: 96%
“…Cleavage at this site in response to farnesol-induced apoptosis in CHO cells excluded CCTa from the nucleus but did not affect in vitro activity [185,218]. In contrast, caspase cleavage of CCTa in P. aeruginosa-infected murine lung epithelial cells was linked to decreased PC synthesis and apoptosis [219]. A more extensive analysis of inhibition of the CDP-choline pathway in apoptotic cells revealed that caspase 3 cleavage of CCTa is not required for inhibition of PC synthesis [218].…”
Section: Ccta Translocation Between Nuclear and Cytoplasmic Compartmentsmentioning
confidence: 96%
“…Mucoid strains also inhibit gene transcription of SP-B and SP-C, compounding surfactant deficiency that impairs stability of surfactant films [59]. In addition, other components of gram-negative bacteria, such as LPS inhibit phospholipid synthesis and secretion [59, 60]. Bacterial suppression of surfactant production may also be indirect via release of host cell cytokines, including tumor necrosis factor -α, which targets surfactant biosynthetic enzymes for degradation[5760].…”
Section: Role Of Infection On Surfactant Compositionmentioning
confidence: 99%
“…CCT␣ protein turnover might be a physiologically important control mechanism, since the enzyme is degraded by calciumactivated neutral proteinases (calpains) and death effector caspases (7)(8)(9). Calpain severs CCT␣ at the amino terminus and within the catalytic domain-membrane binding domain boundary (7).…”
mentioning
confidence: 99%